PENGARUH MANAJEMEN MUTU, INOVASI PRODUK, DAN INOVASI PROSES TERHADAP KEUNGGULAN KOMPETITIF USAHA MIKRO, KECIL, DAN MENENGAH DI DAERAH GROGOL, JAKARTA BARAT - Yustinus Yuniarto; Oktafalia Marisa (STIE Wiyatamandala, 2018)
This research based on data of UMKM business in Indonesia. Based on this data UMKM in Indonesia gave significant contribution to Indonesia economics. Unfortunately, this growth is not supported by sustainability of the business itself. It still lacks of surviving ability and many of it finally failed. In this research we examined the influence of quality management to the product innovation and innovation process itself. Further more we examined the influence of product innovation and innovation process to competitive advantages of restaurant business. We examined 112 restaurants as the sample in this research. Most of sample is in Grogol, West Jakarta. This research analyzed using SEM-PLS and Wrap PLS 6.0. Finding of this research is quality management affect product innovation and innovation process. We also find product innovation and innovation process to competitive advantages of the restaurant. Keyword: UMKM, Quality Management, Innovation, Competitive Advantages